AQUEOUS HUMOR CYTOKINE LEVELS AND REBOUND MACULAR EDEMA AFTER CONBERCEPT TREATMENT IN PATIENTS WITH CENTRAL RETINAL VEIN OCCLUSION. Issue 4 (April 2021) - Yang, Kai-Bo; Sun, Xu-Yang; Sun, Li-Ping; Li, Jun; Liu, Zhe-Li; Zhang, Han
Abstract : Purpose: This study aimed to investigate the effect of intravitreal conbercept (IVC) injections on the aqueous humor concentrations of angiogenic and inflammatory cytokines in patients with macular edema (ME) due to central retinal vein occlusion and to determine whether changes in cytokine levels after IVC are associated with the development of rebound ME. Methods: Forty-nine patients with ME caused by central retinal vein occlusion were included in this retrospective study. Monthly doses of IVC were administered for three months, followed by a Pro Re Nata dosing regimen. Rebound ME was defined as ≥110% increase in the foveal thickness compared with the baseline. Whenever injections were administered, aqueous humor samples were obtained. Multiplex bead assay was used to measure seven angiogenic and inflammatory cytokines in aqueous humor samples. Results: At baseline, patients with central retinal vein occlusion showed significantly higher aqueous humor concentrations of vascular endothelial growth factor, placental growth factor, monocyte chemoattractant protein-1, platelet-derived growth factor-AA, IL-6, IL-8, and IL-12. At 1-month and 2-month follow-up after IVC, significantly decreased concentrations of all cytokines were observed. During the 12-month follow-up period, 6 of the 49 eyes (12.2%) showed rebound ME after IVC. Patients with rebound ME showed significantly elevated levels of inflammatory but not angiogenic cytokines. Conclusion: Angiogenic and inflammatory cytokines were overexpressed in patients with ME caused by central retinal vein occlusion. Conbercept treatment influenced the concentrations of various inflammatory cytokines and reduced aqueous vascular endothelial growth factor and placental growth factor concentrations. Rebound ME may occur due to disruption of the balance between angiogenic and inflammatory cytokines and an accompanying excess of inflammatory cytokines but not angiogenic cytokines, after antivascular endothelial growth factor therapy. Abstract : Our results suggest that disruption of the balance between angiogenic and inflammatory cytokines after antivascular endothelial growth factor therapy and the accompanying excess of inflammatory cytokines levels in some patients may lead to rebound macular edema and may lead to switching agents and personalizing medicine.